The Artist-Enterprise in the Digital Age - Greffe, Xavier (Creativity, Heritage and the City,, 2017)
This book is a monograph of cultural economics of a new concept, artist-enterprises. It explores various dimensions that artists embody, i.e., aesthetic, critical, messianic, and economic ones, and screens the multiple challenges faced by the artist-enterprises in terms of pricing, funding, and networking in the Digital Age. It shows how these artist-enterprises are at the core of the contemporary creative industries. Even when they are on their own, artists have to demonstrate or manage a variety of skills, sign contracts both in the early and later stages of their activities, and also maintain relationships and networks that enable them to attain their artistic and economic goals. They are no longer simply entrepreneurs managing their own skills but are the enterprises themselves. The artist-enterprises thus find themselves at the confluence of two dynamics of production-artistic and economic: artistic because they invent new expressions and meanings; and economic because these expressions must be supported by monetary values on the market. The artistic dynamic is part of a long process of artistic enhancement and only an artist can say whether it has reached the point of presentation or equilibrium. The economic dynamic is dependent on the constant endorsement of artists' works by the market to ensure their survival as artist-enterprises. The tension created by this disparity is further aggravated by another tension: the need to overcome a number of risks so that artist-enterprises can progress. This book will be of special interest to artists, managers, students, professionals, and researchers in the fields of the arts, creativity, economics, and development. The author is Emeritus Professor at the University Paris I Panthéon-Sorbonne.